If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 = 16 + 3j Solving 49 = 16 + 3j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-3j' to each side of the equation. 49 + -3j = 16 + 3j + -3j Combine like terms: 3j + -3j = 0 49 + -3j = 16 + 0 49 + -3j = 16 Add '-49' to each side of the equation. 49 + -49 + -3j = 16 + -49 Combine like terms: 49 + -49 = 0 0 + -3j = 16 + -49 -3j = 16 + -49 Combine like terms: 16 + -49 = -33 -3j = -33 Divide each side by '-3'. j = 11 Simplifying j = 11
| -10=x-17 | | -7-5(8n*8)=193 | | 6=d/7 | | -2x=-26 | | 4x^2+3x-76=0 | | 9+5.50x=y | | -3h-4.2=55-11h | | n-16=-8 | | 15+2h=9 | | s/49=10/14 | | 56+8w=2w+16 | | 35=7+4s | | 4x+3y=22 | | 7[2-(3+4r)]-2r=-9+2(1-15r) | | 11+7h=4 | | r-16=-23 | | 27a+16=-73/5 | | x+6y-9x-13y+2x= | | -9h+12=-24 | | -1=n-4 | | 12y=21/4 | | 9(2x-6)=3(6x+1) | | 7(5+c)=6(c-1) | | -17+3y=51 | | (8f)/(6f) | | 8f/6f | | 6y-6=3y+9 | | n/2=12 | | 14+-8t=1328 | | 4(x+9)-4whenx=3 | | 9x+8=-64 | | -25-4c=17 |